FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA DI DESA KOMBANGAN KECAMATAN GEGER KABUPATEN BANGKALAN - Karimia, Himiyatul; Arisinta, Octaviana; Ulum, Romiftahul (STKIP Persada Khatulistiwa Sintang, 2023)
One of the variables influencing MSME revenue is capital. Capital, working hours, and length of business are thought to influence the income of street vendors in Kombangan village, Geger subdistrict, according to this study. The purpose of this study is to identify the elements that influence the revenue level of street vendors in Kombangan village, Geger subdistrict. The study methods utilized include quantitative methods, The research population comprised all street vendors in Kombangan village, Geger sub-district, Bangkalan district, and the sample size was 30 street vendors. In this study, the free variables are capital, hours of work, and length of job, while the bound variable is income. The instrument in this study is a lift. Data analysis used is validity test, rehabilitation test, double linear regression analysis, normality test T test, F test, determination coefficient analysis. The results of the research show that partly capital and working hours have no influence on income; while long business influence income variables; Capital, Working Hours, and Business Length all have a beneficial impact on the income of street vendors in Kembangan village, Geger sub-district, Bangkalan district.